ICTV Virus Taxonomy Profile: Avsunviroidae - Di Serio, Francesco; Li, Shi-Fang; Matoušek, Jaroslav; Owens, Robert A; Pallás, Vicente; Randles, John W; Sano, Teruo; Verhoeven, Jacobus Th J; Vidalakis, Georgios; Flores, Ricardo; Ictv Report Consortium (The Journal of general virology, 2018)
Members of the family Avsunviroidae have a single-stranded circular RNA genome that adopts a rod-like or branched conformation and can form, in the strands of either polarity, hammerhead ribozymes involved in their replication in plastids through a symmetrical RNA-RNA rolling-circle mechanism. These viroids lack the central conserved region typical of members of the family Pospiviroidae. The family Avsunviroidae includes three genera, Avsunviroid, Pelamoviroid and Elaviroid, with a total of four species. This is a summary of the ICTV Report on the taxonomy of the family Avsunviroidae, which is available at http://www.ictv.global/report/avsunviroidae.
Keywords: Genome, Viral; eggplant latent viroid; taxonomy; genom virový; RNA katalytická; RNA, Viral; replikace viru; peach latent mosaic viroid; replikace DNA; viroidy; viroid; ICTV; RNA; kruhová RNA; RNA, Circular; RNA, Catalytic; RNA virová; Avsunviroidae; Viroids; avocado sunblotch viroid; Virus Replication; DNA Replication